Mixing and Interfacial Composition in Polymer/Fullerene Thin Films - Elizabeth L. Hynes (2018)
Organic photovoltaic (OPV) devices use polymers and small-molecules, such as fullerenes,and offer an alternative to conventional inorganic devices. To achieve commercial success OPV devices require well-controlled morphologies and increased device lifetimes. The film morphology of these devices is complex: both mixing and crystallisation can occur. In this thesis, the fundamental behaviour of two model polymer/fullerene systems is investigated. The impact of parameters such as film thickness, molecular weight (MW) of the polymer and annealing temperature, on crystallisation and mixing are examined.The effect of MW on the mixing and interface width (between phases with different compositions) in fullerene/polymer systems is presented. These effects are examined in polymer/fullerene bilayers that are annealed at a range of temperatures close to or a few tens of degrees above the (bulk) glass transition temperatures of the materials. Neutron reflectivity is used to probe the composition profile within bilayer thin-films, and optical microscopy and atomic force microscopy (AFM) are used to observe crystal morphology. The fullerenes used are phenyl-C60-butyric acid methyl ester (PCBM) and bis-adduct phenyl-C60-butyric acid methyl ester (bis-PCBM). The polymer used is polystyrene (PS) which is chosen due to its low polydispersity and well-characterised behaviour in thin-films. Stable bilayer composition profiles are observed after annealing, and significant evidence is found for an MW dependence of the interfacial width. The observed behaviour supports the hypothesis that these systems represent a liquid-liquid equilibrium. The behaviour is also found to be broadly in agreement with theoretical predictions.Preliminary evidence is also presented regarding the impact of fullerene oxidation on mixing in these systems, which is observed to have a significant MW-dependence. Annealing at higher temperatures (well above the glass transition temperature of the materials) results in the growth of large (micron-sized) fullerene crystals in PCBM/PS bilayer samples. The observed morphologies of these crystals are found to be dependent on the PCBM layer thickness.